2018
DOI: 10.1021/acs.molpharmaceut.8b00765
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis Pathways of Endothelial Cell Derived Exosomes

Abstract: Nanosized extracellular vesicles (EVs) possess the natural machinery needed to enter selectively, and transmit complex molecular messages efficiently into targeted cells. The intracellular fate of the vesicular cargos depends on the route of internalization. Therefore, understanding the mechanism of attachment and subsequent intake of these vesicles (before and after exerting any modification) is imperative. Here the extent of communication, the uptake kinetics and the pathways of endothelial EVs into endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 24 publications
0
23
0
3
Order By: Relevance
“…The three classical endocytic pathways are clathrin‐mediated, caveolin‐mediated endocytosis and macropinocytosis . Recent work has indicated that all three of these pathways can mediate occludin internalization in intestinal epithelial TJ, depending on the type of stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The three classical endocytic pathways are clathrin‐mediated, caveolin‐mediated endocytosis and macropinocytosis . Recent work has indicated that all three of these pathways can mediate occludin internalization in intestinal epithelial TJ, depending on the type of stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the actin cytoskeleton using Cytochalasin D or Lantrunculin A inhibited sEV uptake by Human Umbilical Vein Cells (HUVECs), confirming that an intact cytoskeleton facilitates sEV internalization [ 93 ]. Chlorpromazine, which blocks clathrin-mediated endocytosis, inhibited sEV uptake by ovarian cancer cells [ 94 ] and endothelial cells [ 95 ], and heparin dose-dependently inhibited sEV uptake by glioblastoma (GBM) cells [ 96 ] and bone marrow stromal cells [ 97 ]. These findings reinforce the notion that targeting the uptake of cancer sEVs is a promising strategy in the development of new cancer therapeutics, and future efforts should focus on small molecules capable of inhibiting cancer sEV uptake and suppressing tumor progression.…”
Section: Evs As Potential Therapeutic Targets In Cancermentioning
confidence: 99%
“…Exosomes are nanosized vesicles (40–160 nm in diameter), whereas ectosomes are larger and more diverse (50 nm–1 μm in diameter) ( Trams et al., 1981 ). Exosomes are derived from the endocytic pathway and the Golgi apparatus ( Banizs et al., 2018 ; Nagano et al., 2019 ). Ectosomes, on the other hand, are formed by direct host cell liberation of the plasma membrane via outward budding and pinching ( Heijnen et al., 1999 ).…”
Section: Ev Biogenesis and Uptakementioning
confidence: 99%